Bank Risk Profile and Credit Growth in Indonesia - Gurendrawati, Etty; Khairunnisa, Hera; Ulupui, I Gusti Ketut Agung; Suryarini, Trisni; Zakaria, Adam (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 16 No 1 (2021), 2021)
Banks are one of the important industries in a country, whose importance is evidenced by the management of bank risks. The purpose of this research is to investigate the effect or impact of the risk profile disclosure on banking credit growth in Indonesia for the years 2016, 2017, and 2018. Commercial banks in Indonesia, which provide information related to a complete risk profile in the annual report from 2016 to 2018, were selected as the sample. The risk profile variable is an independent variable consisting of credit risk, market risk, and liquidity risk. Panel data regression with E-Views 8 was used for data processing. The results of the study prove that disclosure of credit risk, market risk, and liquidity have significant influences to the banking credit growth in Indonesia.